2016
DOI: 10.1002/jca.21472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic plasma exchange on early allograft dysfunction after liver transplantation

Abstract: TPE effectively removed plasma bilirubin and improved coagulation function in EAD patients, with higher survival in the TPE group than in the non-TPE group. TPE may be an effective liver support for EAD patients. J. Clin. Apheresis 32:147-153, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…A few reports have suggested the efficacy of TPE in liver support. 10,[14][15][16][17] In this regard, TPE can be used as a temporary support in liver failure until graft recovery or retransplantation. According to a report from Johns Hopkins Hospital, TPE provided an effective treatment option for dysfunctional liver allograft in four of five patients, and all four patients had functioning grafts 1 year after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports have suggested the efficacy of TPE in liver support. 10,[14][15][16][17] In this regard, TPE can be used as a temporary support in liver failure until graft recovery or retransplantation. According to a report from Johns Hopkins Hospital, TPE provided an effective treatment option for dysfunctional liver allograft in four of five patients, and all four patients had functioning grafts 1 year after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no ASFA (American Society for Apheresis) 9 guidelines for the use of TPE for liver graft dysfunction in the setting hyperbilirubinemia, the decision to proceed with TPE was based on our institution's experience with managing similar situations and published literature demonstrating the utility of early TPE in liver graft dysfunction by removing excess bilirubin. 10 After obtaining informed consent, TPE was performed using the COBE Spectra apheresis system processing one blood volume with thawed plasma replacement (2600 mL) to reduce the risk of bleeding from worsening thrombocytopenia and coagulopathy. A central venous catheter was placed in the left internal jugular (IJ) vein for vascular access.…”
Section: Case Historymentioning
confidence: 99%
“…Studies of the treatment of hyperbilirubinemia after liver transplantation are limited. Choe et al [12] reported that therapeutic plasma exchange effectively removed plasma bilirubin and improved survival. Steroids are used to ameliorate hyperbilirubinemia in biliary atresia before and after transplantation [22,23], but studies are lacking to confirm its effect on hyperbilirubinemia after adult liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative hyperbilirubinemia is also a risk factor for graft loss in liver transplantation [8,9]. Although many studies have reported risk factors [3,10] and prevention strategies [11] for early graft dysfunction, few studies have investigated the treatment of hyperbilirubinemia caused by graft dysfunction [12].…”
Section: Introductionmentioning
confidence: 99%
“…The flow rate was roughly 40 ml/min, adjusted based on patient’s tolerance. Calcium gluconate was infused at a rate of 10–20 mg/h during the entire TPE period, titrated individually for each patient to prevent and treat adverse effects of hypocalcaemia 55 , 56 .…”
Section: Methodsmentioning
confidence: 99%